2013
DOI: 10.1115/1.4027340
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Transfer and Thermal Dose Using Magnetic Nanoparticles During HIFU Thermal Ablation—An In-Vitro Study

Abstract: Avoiding collateral damage to healthy tissues during the high intensity focused ultrasound (HIFU) ablation of malignant tumors is one of the major challenges for effective thermal therapy. Such collateral damage can originate out of the need for using higher acoustic powers to treat deep seated or highly vascularized tumors. The objective of this study is to assess the utility of using magnetic nanoparticles (mNPs) during HIFU procedures to locally enhance heating at low powers, thereby reducing the likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In particular, the achievement of elevated temperatures when the region of interest is deep or hypervascularized can be problematic. Actually, a solution could be to enhance the acoustic power or the exposition time, however it would increase the risk of side effects, as skin burns and nerve injury [ 47 , 48 ]. Thus, various types of micro and nano–bubbles [ 49 ], as well as other particles [ 50 ], were proposed in combination with HIFU for therapy and diagnostic imaging.…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the achievement of elevated temperatures when the region of interest is deep or hypervascularized can be problematic. Actually, a solution could be to enhance the acoustic power or the exposition time, however it would increase the risk of side effects, as skin burns and nerve injury [ 47 , 48 ]. Thus, various types of micro and nano–bubbles [ 49 ], as well as other particles [ 50 ], were proposed in combination with HIFU for therapy and diagnostic imaging.…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
“…These structures are indeed able to enhance HIFU-associated mechanical effects, providing cavitation nuclei [ 48 ]. Furthermore, they increase the acoustic attenuation with a consequent temperature rise [ 51 ], reducing the ultrasound intensity and the exposure time required to obtain bioeffects [ 47 ].…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
“…Also, magnetic NPs could be used for SDT [148,155,156]. Ebrahimi et al investigated the sonodynamic properties of iron oxide nanoparticles in a breast carcinoma cell line.…”
Section: Ultrasound-responsive Npsmentioning
confidence: 99%
“…The amount of absorbed ultrasound energy for the 0.0625% mNPs and 0.125% gNPs, derived from the initial slope of the temperature trace [13], is provided in Table 2. An initial time of 2.5 s is chosen to compute the slopes.…”
Section: Resultsmentioning
confidence: 99%
“…One strategy for reducing the adverse effects associated with high intensities and long exposure times in HIFU ablation procedures is to introduce microcapsules and nanoparticles (NPs) at the tumor site [13,14]. Sun et al [15,16] reported the effects of PLGA-coated Fe 3 O 4 microcapsules in HIFU therapy and have found enhancement in hyperthermia due to the microcapsules.…”
Section: Introductionmentioning
confidence: 99%